High-CTI (comparative tracking index) and high-glowing filament flame-retardant PC (polycarbonate) composite material and preparation method thereof

By using silicon copolymerized polycarbonate, random copolymerized polypropylene, linear low-density polyethylene and thermoplastic elastomer in polycarbonate materials, combined with the addition of inorganic substances, the properties of CTI and glow wire of polycarbonate materials are solved. The overall performance improvement of high CTI and high glow wire has been achieved.

CN119463446APending Publication Date: 2025-02-18中化工程塑料(扬州)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411741389.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing polycarbonate (PC) materials have low CTI, making it difficult to meet the CTI requirements of high-pressure components and the carbon-forming ability of glow wire tests at the same time.

Method used

Silicon copolymer polycarbonate (Si-PC), random copolymer polypropylene (PP), linear low-density polyethylene (LLDPE) and styrene-ethylene-propylene-styrene thermoplastic elastomer (SEPS) are used to reduce the material The aromatic group content blocks carbonization continuity and improves CTI performance. At the same time, inorganic substances such as calcium carbonate, talc and boehmite are added to improve flame retardant properties.

Benefits of technology

It achieves high CTI (up to 600V) and high glow wire performance (GWIT 1.0mm to 900°C) of polycarbonate materials, while maintaining excellent appearance and processing performance, suitable for high pressure and flame retardant requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162677070000021
    Figure BDA0005162677070000021
  • Figure BDA0005162677070000022
    Figure BDA0005162677070000022
  • Figure BDA0005162677070000051
    Figure BDA0005162677070000051
Patent Text Reader

Abstract

The invention provides a flame-retardant PC (polycarbonate) composite material and a preparation method thereof. Comprising 100 parts by weight of polycarbonate, 100 parts by weight of silicon copolymerized polycarbonate, 5-10 parts by weight of polypropylene, 5-10 parts by weight of polyethylene, 5-10 parts by weight of a styrene-ethylene-propylene-styrene thermoplastic elastomer, 8-15 parts by weight of a phosphorus flame retardant, 5-10 parts by weight of calcium carbonate, 5-10 parts by weight of talcum powder and 1-4 parts by weight of boehmite. Meanwhile, the invention also provides a corresponding preparation method. According to the polycarbonate material provided by the invention, through the synergistic effect of the components, the obtained polycarbonate material has the characteristics of high CTI (Comparative Tracking Index) and high glowing filament, the CTI can reach 600V, the glowing filament (GWIT) can reach 900 DEG C at 1.0 mm, and the polycarbonate material also has excellent appearance and good processability, and is suitable for being applied to the field having requirements on high pressure and flame retardance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polycarbonate resin composite materials, and relates to a flame retardant PC composite material and a preparation method thereof, and in particular to a high CTI, high glow-wire flame retardant PC composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC) is a type of thermoplastic engineering plastic with excellent heat resistance and impact resistance. It is currently widely used in various fields such as automobiles, electronic appliances, etc.

[0003] Since PC materials contain aromatic groups, they have a high carbonization property after tracking, which makes it easy to form an electrical path and cause failure when testing CTI (polymer tracking index). Generally, the CTI of conventional PC is around 200V, while the use of many high-voltage components requires the CTI to reach more than 600V, so its application in such scenarios is greatly limited.

[0004] In order to solve the problem of low CTI of PC materials, it is usually necessary to reduce the charring ability of PC materials at high temperatures, but this also reduces the flame retardant properties of the material itself. In particular, when PC materials need to pass glow-wire tests, the material itself needs to have good charring ability to improve the flame retardant energy absorption of the material. When the application scenario requires PC materials to meet both CTI and glow-wire tests, it is often difficult to meet the requirements.

[0005] The prior art also discloses some patents on high CTI, glow-wire flame-retardant PC materials. Chinese patent CN111171548A discloses a high CTI, low-temperature super-tough flame-retardant PC material and a preparation method thereof, which includes the following components: 44-66% PC resin, 20-30% silicon-containing PC resin, 5-8% phosphorus flame retardant, 8-15% high CTI additive, 0.1-1% antioxidant, 0.1-1% lubricant and 0.2-1% anti-dripping agent. However, the high CTI additive of the patent contains more polytetrafluoroethylene (PTFE), the product cost is high, it is not good for the appearance of PC products, and there are certain difficulties in processing.

[0006] Chinese patent CN108129825A discloses a high CTI, high heat-resistant halogen-free flame-retardant PC / ABS composition and a preparation method thereof. The components are composed as follows in parts by weight: 65-90 parts by weight of polycarbonate; 3-10 parts by weight of ABS resin; 4-10 parts by weight of homemade phosphorus silicon polymer; 3-10 parts by weight of modified porous material; 1-5 parts by weight of toughening agent; 0.1-0.3 parts by weight of antioxidant; 0.3-0.7 parts by weight of anti-drip agent; 0.2-0.5 parts by weight of lubricant. However, the addition of ABS component in this patent causes the heat resistance of the product to decrease, and the CTI value cannot reach the requirement of 600V.

[0007] Therefore, how to find a more suitable polycarbonate resin composite material, a flame-retardant PC composite material with excellent CTI and glow-wire performance is very necessary, and better broaden the breadth and depth of its application, has become one of the urgent problems to be solved by many researchers in this field. Summary of the invention

[0008] In view of this, the technical problem to be solved by the present invention is to provide a flame retardant PC composite material and a preparation method thereof, in particular a high CTI, high glow-wire flame retardant PC composite material. The polycarbonate material provided by the present invention has the characteristics of high CTI and high glow-wire; at the same time, the process is simple and easy to control, which is conducive to the realization of industrial continuous production.

[0009] The present invention provides a flame retardant PC composite material, which comprises, by weight of raw materials:

[0010]

[0011] Styrene-ethylene-propylene-styrene thermoplastic elastomer (SEPS): 5 to 10 parts by weight;

[0012]

[0013] Preferably, the polycarbonate comprises a phosgene polymerized polycarbonate;

[0014] The melt index of the polycarbonate is 40 to 60 g / min, and the test conditions are 300° C.×1.2 kg (ISO1133);

[0015] The styrene mass content of the styrene-ethylene-propylene-styrene thermoplastic elastomer is 30% to 40%.

[0016] Preferably, the silicon content of the silicon copolymer polycarbonate is 4% to 6% by mass;

[0017] The melt index of the silicon copolymer polycarbonate is 8 to 15 g / 10 min, and the test conditions are 300° C.×1.2 kg (ISO1133);

[0018] The phosphorus-based flame retardants include triphenyl phosphate (TPP), resorcinol bisdiphenyl phosphate (RDP) and hexaphenylepoxy triphosphazene (HPCP).

[0019] Preferably, the polypropylene comprises random copolymer polypropylene;

[0020] The melt index of the polypropylene is 1-3 g / 10 min, and the test conditions are 230° C.×2.16 kg (ISO1133).

[0021] Preferably, the polyethylene comprises linear low-density polyethylene;

[0022] The melt index of the polyethylene is 1-3 g / 10 min, and the test conditions are 230° C.×2.16 kg (ISO1133).

[0023] Preferably, the calcium carbonate comprises heavy calcium carbonate;

[0024] The particle size of the calcium carbonate is 2.8 to 3.5 μm;

[0025] The specific surface area of ​​the boehmite is 2.0 to 6.0 m 2 / g.

[0026] Preferably, the talc powder comprises ultrafine talc powder;

[0027] The mesh size of the talcum powder is 5000-8000 meshes.

[0028] The present invention provides a method for preparing a flame retardant PC composite material as described in any one of the above technical solutions, comprising the following steps:

[0029] 1) mixing polycarbonate, silicon copolymer polycarbonate, polypropylene, polyethylene, styrene-ethylene-propylene-styrene thermoplastic elastomer and a portion of phosphorus-based flame retardant to obtain a first mixture;

[0030] Mixing calcium carbonate, talc and boehmite to obtain a second mixture;

[0031] and mixing another portion of the phosphorus-based flame retardant to prepare a third mixture;

[0032] 2) The first mixture obtained in the above step is added from the main feed port of the extruder, the second mixture is added from the side feed port of the middle section of the extruder, and the third mixture is added from the side feed port of the next section of the extruder. After extrusion and granulation, a flame retardant PC composite material is obtained.

[0033] Preferably, the portion of phosphorus-based flame retardants includes triphenyl phosphate;

[0034] The other part of the phosphorus-based flame retardant includes resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene;

[0035] The mass ratio of the triphenyl phosphate, resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene is 1:1:1.

[0036] Preferably, the middle section is the fifth section of the extruder;

[0037] The next section is the sixth section of the extruder;

[0038] The extrusion temperature is 265-280°C;

[0039] The extrusion speed is 500-600 r / min.

[0040] The present invention provides a flame retardant PC composite material, which comprises, by weight of raw materials, 100 parts by weight of polycarbonate, 100 parts by weight of silicon copolymer polycarbonate, 5 to 10 parts by weight of polypropylene, 5 to 10 parts by weight of polyethylene, 5 to 10 parts by weight of styrene-ethylene-propylene-styrene thermoplastic elastomer, 8 to 15 parts by weight of phosphorus flame retardant, 5 to 10 parts by weight of calcium carbonate, 5 to 10 parts by weight of talc and 1 to 4 parts by weight of boehmite. Compared with the prior art, in order to solve the problem of low CTI of flame retardant PC material, the present invention particularly adopts silicon copolymer polycarbonate (Si-PC), random copolymer polypropylene (PP), linear low-density polyethylene (LLDPE) and styrene-ethylene-propylene-styrene thermoplastic elastomer (SEPS) to reduce the content of aromatic groups in the whole material, which reduces the carbonization of the material after electrical tracking on the one hand, and blocks the carbonization continuity on the surface of the material on the other hand, prevents the formation of electrical path, thereby improving the CTI performance of the material.

[0041] The present invention adopts random copolymerized polypropylene, which has very low crystallinity and the forming process of non-crystalline material PC. The aggregated structures of the two are closer, while LLDPE has low crystallinity and higher branching degree, which is conducive to reducing the continuity of material carbonization in three-dimensional space. The three cooperate with each other, and further add SEPS, using the characteristics of good compatibility between styrene and PC materials in its chain segments, and good compatibility between ethylene and propylene segments and PP and PE, to play the role of compatibilizer and build a "bridge" between PC and PP and PE. The four cooperate with each other, which not only solves the compatibility problem when PC and PP and PE materials are shared, improves the overall performance of the material, but also solves the problem that the processing temperature difference between PC and olefin materials is too large, the compatibility is too poor, and a uniformly dispersed structure cannot be formed, resulting in the problem that the appearance of the material is easy to peel. Finally, the material system prepared by the present invention has a CTI of 600V when very little olefin is added, avoiding a significant decrease in the glow wire performance of the material.

[0042] Furthermore, the present invention also specifically uses a silicon copolymer polycarbonate with a silicon content of 4% to 6% to act together with the above-mentioned olefins on a carbonate matrix, and utilizes the smaller domain size (10 to 20 nm) of dimethylsiloxane and a more uniform distribution. After the material is electro-tracked, it can well block the continuity of carbonization and prevent the formation of an electrical path. In collaboration with olefins, the problem of a lower glow wire of the material after the addition of olefin materials is avoided, thereby ensuring the carbonization performance required by the glow wire and avoiding too low CTI.

[0043] Furthermore, the present invention improves the flame retardancy of the material by adding inorganic substances such as calcium carbonate, talc, boehmite, etc., which act together with the above-mentioned olefins on the carbonate matrix. On the one hand, the content of the aromatic group of the PC material is diluted. On the other hand, these specific inorganic fillers can be better coated with the resin to achieve dispersion, thereby avoiding the continuity of the PC resin carbon layer on the surface of the material and affecting the CTI performance of the material. At the same time, the compounding of these inorganic substances improves the flame retardancy of the material and helps improve the glow-wire performance, thereby further improving the glow-wire and CTI performance of the material.

[0044] In addition, in order to maintain an excellent flame retardant effect without affecting the performance of the CTI of the material, the present invention uses a compound flame retardant, triphenyl phosphate (TPP), resorcinol bis diphenyl phosphate (RDP) and hexaphenyl epoxy triphosphazene (HPCP) are compounded in a mass ratio of 1:1:1, and the difference in carbonization efficiency of TPP, RDP and HPCP at high temperature is used to achieve an intermittent carbonization effect on the surface of the material, which can maintain high flame retardancy and avoid directly forming a complete electrical path. In addition, combined with the addition of calcium carbonate, it can have a good heat absorption effect, and talcum powder can generate water vapor. During the combustion process of the material, the continuous carbon layer needs to be destroyed to help achieve a high CTI.

[0045] Experimental results show that the polycarbonate material provided by the present invention, through the synergistic effect of the above components, can obtain a polycarbonate with a CTI of 600V and a glow wire (GWIT) of 1.0mm of 900°C, an excellent appearance, and good processing performance, and is suitable for applications in fields requiring high pressure and flame retardancy. DETAILED DESCRIPTION

[0046] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0047] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0048] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity requirements in the field of polycarbonate resin material preparation.

[0049] The brands and abbreviations of all raw materials of the present invention are conventional brands and abbreviations in the art. Each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.

[0050] The present invention provides a flame retardant PC composite material, which comprises, by weight of raw materials:

[0051]

[0052] In the present invention, the amount of polypropylene added is 5 to 10 parts by weight, can be 6 to 9 parts by weight, can be 7 to 8 parts by weight.

[0053] In the present invention, the amount of polyethylene added is 5 to 10 parts by weight, can be 6 to 9 parts by weight, can be 7 to 8 parts by weight.

[0054] In the present invention, the added amount of the styrene-ethylene-propylene-styrene thermoplastic elastomer is 5 to 10 parts by weight, can be 6 to 9 parts by weight, can be 7 to 8 parts by weight.

[0055] In the present invention, the phosphorus-based flame retardant is added in an amount of 8 to 15 parts by weight, 9 to 13 parts by weight, or 10 to 12 parts by weight.

[0056] In the present invention, the added amount of calcium carbonate is 5 to 10 parts by weight, can be 6 to 9 parts by weight, can be 7 to 8 parts by weight.

[0057] In the present invention, the added amount of the talc powder is 5 to 10 parts by weight, can be 6 to 9 parts by weight, can be 7 to 8 parts by weight.

[0058] In the present invention, the amount of boehmite added is 1 to 4 parts by weight, can be 1.5 to 3.5 parts by weight, or can be 2 to 3 parts by weight.

[0059] In the present invention, the polycarbonate preferably includes phosgene-polymerized polycarbonate.

[0060] In the present invention, the melt index of the polycarbonate is preferably 40 to 60 g / min, more preferably 44 to 56 g / min, and more preferably 48 to 52 g / min. The test conditions are 300° C.×1.2 kg (ISO1133).

[0061] In the present invention, the styrene mass content of the styrene-ethylene-propylene-styrene thermoplastic elastomer is preferably 30% to 40%, more preferably 32% to 38%, and more preferably 34% to 36%.

[0062] In the present invention, the silicon content of the silicon copolymer polycarbonate is preferably 4% to 6%, more preferably 4.4% to 5.6%, and more preferably 4.8% to 5.2%.

[0063] In the present invention, the melt index of the silicon copolymer polycarbonate is preferably 8 to 15 g / 10 min, more preferably 9 to 14 g / 10 min, more preferably 10 to 13 g / 10 min, and more preferably 11 to 12 g / 10 min. The test conditions are 300° C.×1.2 kg (ISO1133).

[0064] In the present invention, the phosphorus-based flame retardant preferably includes triphenyl phosphate, resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene.

[0065] In the present invention, the polypropylene preferably includes random copolymer polypropylene.

[0066] In the present invention, the melt index of the polypropylene is preferably 1 to 3 g / 10 min, more preferably 1.4 to 2.6 g / 10 min, and more preferably 1.8 to 2.2 g / 10 min. The test conditions are 230° C.×2.16 kg (ISO1133).

[0067] In the present invention, the polyethylene preferably comprises linear low density polyethylene.

[0068] In the present invention, the melt index of the polyethylene is preferably 1 to 3 g / 10 min, more preferably 1.4 to 2.6 g / 10 min, and more preferably 1.8 to 2.2 g / 10 min. The test conditions are 230° C.×2.16 kg (ISO1133).

[0069] In the present invention, the calcium carbonate preferably includes heavy calcium carbonate.

[0070] In the present invention, the particle size of the calcium carbonate is preferably 2.8 to 3.5 μm, more preferably 2.9 to 3.4 μm, more preferably 3.0 to 3.3 μm, and more preferably 3.1 to 3.2 μm.

[0071] In the present invention, the specific surface area of ​​the boehmite is preferably 2.0 to 6.0 m 2 / g, more preferably 2.5 to 5.5 m 2 / g, more preferably 3.0 to 5.0 m 2 / g, more preferably 3.5 to 4.5 m 2 / g.

[0072] In the present invention, the talc preferably includes ultrafine talc.

[0073] In the present invention, the mesh size of the talc is preferably 5000-8000 mesh, more preferably 5500-7500 mesh, and more preferably 6000-7000 mesh.

[0074] In the present invention, the flame retardant PC composite material is preferably a high CTI, high glow-wire flame retardant PC composite material.

[0075] The present invention provides a method for preparing a flame retardant PC composite material as described in any one of the above technical solutions, comprising the following steps:

[0076] 1) mixing polycarbonate, silicon copolymer polycarbonate, polypropylene, polyethylene, styrene-ethylene-propylene-styrene thermoplastic elastomer and a portion of phosphorus-based flame retardant to obtain a first mixture;

[0077] Mixing calcium carbonate, talc and boehmite to obtain a second mixture;

[0078] and mixing another portion of the phosphorus-based flame retardant to prepare a third mixture;

[0079] 2) The first mixture obtained in the above step is added from the main feed port of the extruder, the second mixture is added from the side feed port of the middle section of the extruder, and the third mixture is added from the side feed port of the next section of the extruder. After extrusion and granulation, a flame retardant PC composite material is obtained.

[0080] The present invention firstly mixes polycarbonate, silicon copolymer polycarbonate, polypropylene, polyethylene, styrene-ethylene-propylene-styrene thermoplastic elastomer and a part of phosphorus flame retardant to obtain a first mixture;

[0081] Mixing calcium carbonate, talc and boehmite to obtain a second mixture;

[0082] Another portion of the phosphorus-based flame retardant is mixed to prepare a third mixture.

[0083] In the present invention, the part of the phosphorus-based flame retardant preferably includes triphenyl phosphate.

[0084] In the present invention, the other part of the phosphorus-based flame retardant preferably includes resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene.

[0085] In the present invention, the mass ratio of triphenyl phosphate, resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene is preferably 1:1:1.

[0086] Finally, the first mixture obtained in the above steps is added from the main feeding port of the extruder, the second mixture is added from the side feeding port of the middle section of the extruder, and the third mixture is added from the side feeding port of the next section of the extruder, and granulated after extrusion to obtain a flame-retardant PC composite material.

[0087] In the present invention, the middle section is preferably the fifth section of the extruder.

[0088] In the present invention, the next section is preferably the sixth section of the extruder.

[0089] In the present invention, the extrusion temperature is preferably 265-280°C, more preferably 268-277°C, and more preferably 271-274°C.

[0090] In the present invention, the extrusion rotation speed is preferably 500-600 r / min, more preferably 520-580 r / min, and more preferably 540-560 r / min.

[0091] The present invention is to complete and refine the overall technical solution, better ensure the structure and composition of the flame retardant PC composite material, and further improve the glow wire and CTI of the flame retardant PC composite material. The above-mentioned high CTI, high glow wire flame retardant PC composite material and its preparation method may specifically include the following contents:

[0092] A high CTI, high glow-wire flame-retardant PC material, comprising the following raw materials in parts by weight:

[0093]

[0094] Specifically, the polycarbonate is polycarbonate (PC) polymerized by phosgene method, with a melt index of 40 g / 10 min to 60 g / min and a test condition of 300° C.×1.2 kg (ISO1133), such as Chimei PC-145k.

[0095] Specifically, the silicon copolymer polycarbonate (Si-PC) has a silicon content of 4% to 6%, a melt index of 8g / 10min to 15g / 10min, and a test condition of 300°C×1.2kg (ISO1133), such as Cangzhou Dahua CH9115LT.

[0096] Specifically, the polypropylene (PP) is a random copolymer polypropylene with a melt index of 1 g / 10 min to 3 g / 10 min and a test condition of 230° C.×2.16 kg (ISO1133), such as Formosa Plastics 5012XT.

[0097] Specifically, the polyethylene (PE) is a linear low-density polyethylene with a melt index of 1 g / 10 min to 3 g / 10 min and a test condition of 230° C.×2.16 kg (ISO1133), such as: Sinopec DFDC9050.

[0098] Specifically, the styrene-ethylene-propylene-styrene thermoplastic elastomer (SEPS) has a styrene content of 30% to 40%, such as Li Changrong SEPS 8600U.

[0099] Specifically, the phosphorus-based flame retardant is prepared by compounding triphenyl phosphate (TPP), resorcinol bisdiphenyl phosphate (RDP) and hexaphenylepoxy triphosphazene (HPCP) in a weight ratio of 1:1:1.

[0100] Specifically, the calcium carbonate is heavy calcium carbonate with a particle size of 2.8 to 3.5 μm, such as Omya, ESKAL-15T.

[0101] Specifically, the talc powder is ultrafine talc powder with a mesh size of 5000-8000 mesh, such as Yirui Stone, M05SLC.

[0102] Specifically, the specific surface area of ​​the boehmite is 2.0 to 6.0 m 2 / g, such as Yishitong, BG-613.

[0103] The present invention also provides a method for preparing a polycarbonate composite material, comprising the following steps:

[0104] A) mixing PC, Si-PC, PP, PE, SEPS and TPP according to parts by mass to obtain a first mixture;

[0105] Mixing calcium carbonate, talc and boehmite according to weight proportions to obtain a second mixture;

[0106] Resorcinol bis diphenyl phosphate and hexaphenyl epoxy triphosphazene are mixed according to weight parts to obtain a third mixture;

[0107] B) adding the first mixture from a main feeding port of a twin-screw extruder, adding the second mixture from a side feeding port of the fifth section of the extruder, and adding the third mixture from a side feeding port of the sixth section of the extruder, and granulating after extrusion to obtain a material.

[0108] Specifically, the extrusion temperature is 265-280° C., and the rotation speed is 500-600 r / min.

[0109] The above content of the present invention provides a high CTI, high glow-wire flame-retardant PC composite material and a preparation method thereof. The present invention particularly uses silicon copolymer polycarbonate (Si-PC), random copolymer polypropylene (PP), linear low-density polyethylene (LLDPE) and styrene-ethylene-propylene-styrene thermoplastic elastomer (SEPS) to synergistically reduce the content of aromatic groups in the overall material, which on the one hand reduces the carbonization of the material after electrical tracking, and on the other hand blocks the carbonization continuity on the surface of the material, preventing the formation of an electrical path, thereby improving the CTI performance of the material.

[0110] The present invention adopts random copolymerized polypropylene, which has very low crystallinity and the forming process of non-crystalline material PC. The aggregated structures of the two are closer, while LLDPE has low crystallinity and higher branching degree, which is conducive to reducing the continuity of material carbonization in three-dimensional space. The three cooperate with each other, and further add SEPS, using the characteristics of good compatibility between styrene and PC materials in its chain segments, and good compatibility between ethylene and propylene segments and PP and PE, to play the role of compatibilizer and build a "bridge" between PC and PP and PE. The four cooperate with each other, which not only solves the compatibility problem when PC and PP and PE materials are shared, improves the overall performance of the material, but also solves the problem that the processing temperature difference between PC and olefin materials is too large, the compatibility is too poor, and a uniformly dispersed structure cannot be formed, resulting in the problem that the appearance of the material is easy to peel. Finally, the material system prepared by the present invention has a CTI of 600V when very little olefin is added, avoiding a significant decrease in the glow wire performance of the material.

[0111] Furthermore, the present invention also specifically uses a silicon copolymer polycarbonate with a silicon content of 4% to 6% to act together with the above-mentioned olefins on a carbonate matrix, and utilizes the smaller domain size (10 to 20 nm) of dimethylsiloxane and a more uniform distribution. After the material is electro-tracked, it can well block the continuity of carbonization and prevent the formation of an electrical path. In collaboration with olefins, the problem of a lower glow wire of the material after the addition of olefin materials is avoided, thereby ensuring the carbonization performance required by the glow wire and avoiding too low CTI.

[0112] Furthermore, the present invention improves the flame retardancy of the material by adding inorganic substances such as calcium carbonate, talc, boehmite, etc., which act together with the above-mentioned olefins on the carbonate matrix. On the one hand, the content of the aromatic group of the PC material is diluted. On the other hand, these specific inorganic fillers can be better coated with the resin to achieve dispersion, thereby avoiding the continuity of the PC resin carbon layer on the surface of the material and affecting the CTI performance of the material. At the same time, the compounding of these inorganic substances improves the flame retardancy of the material and helps improve the glow-wire performance, thereby further improving the glow-wire and CTI performance of the material.

[0113] In addition, in order to maintain an excellent flame retardant effect without affecting the performance of the CTI of the material, the present invention uses a compound flame retardant, triphenyl phosphate (TPP), resorcinol bis diphenyl phosphate (RDP) and hexaphenyl epoxy triphosphazene (HPCP) are compounded in a mass ratio of 1:1:1, and the difference in carbonization efficiency of TPP, RDP and HPCP at high temperature is used to achieve an intermittent carbonization effect on the surface of the material, which can maintain high flame retardancy and avoid directly forming a complete electrical path. In addition, combined with the addition of calcium carbonate, it can have a good heat absorption effect, and talcum powder can generate water vapor. During the combustion process of the material, the continuous carbon layer needs to be destroyed to help achieve a high CTI.

[0114] Experimental results show that the polycarbonate material provided by the present invention, through the synergistic effect of the above components, can obtain a polycarbonate with a CTI of 600V and a glow wire (GWIT) of 1.0mm of 900°C, an excellent appearance, and good processing performance, and is suitable for applications in fields requiring high pressure and flame retardancy.

[0115] In order to further illustrate the present invention, a flame retardant PC composite material and a preparation method thereof provided by the present invention are described in detail in combination with embodiments below. However, it should be understood that these embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.

[0116] In the following embodiments:

[0117] PC is synthesized by phosgene method, with a melt index of 40 g / 10 min-60 g / min and a test condition of 300°C x 1.2 kg (ISO1133).

[0118] Si-PC, silicon content is 4% to 6%, melt index is 8g / 10min to 15g / 10min, test conditions are 300°C×1.2kg (ISO1133).

[0119] PP is random copolymer polypropylene (PP-R) with a melt index of 1 g / 10 min to 3 g / 10 min and a test condition of 230°C x 2.16 kg (ISO1133).

[0120] PE is linear low-density polyethylene (LLDPE) with a melt index of 1 g / 10 min to 3 g / 10 min, and the test conditions are 230° C.×2.16 kg (ISO1133).

[0121] SEPS, styrene content 30% to 40%.

[0122] The phosphorus-based flame retardant is prepared by compounding TPP, RDP and HPCP in a ratio of 1:1:1 by mass.

[0123] Calcium carbonate is heavy calcium carbonate with a particle size of 2.8 to 3.5 μm.

[0124] Talc powder is ultrafine talcum powder with a mesh size of 5000 to 8000 mesh.

[0125] Boehmite has a specific surface area of ​​2.0 to 6.0 m 2 / g products.

[0126] Embodiments 1 to 4

[0127] See Table 1, which shows the components and their weight percentages in Examples 1 to 4 of the present invention.

[0128] Table 1

[0129]

[0130]

[0131] The preparation methods of the above embodiments 1 to 4 are as follows:

[0132] A) mixing PC, Si-PC, PP, PE, SEPS and triphenyl phosphate (TPP) to obtain a first mixture;

[0133] mixing calcium carbonate, talc and boehmite to obtain a second mixture;

[0134] Mixing resorcinol bisdiphenyl phosphate (RDP) and hexaphenylepoxy triphosphazene (HPCP) according to weight parts to obtain a third mixture;

[0135] B) adding the first mixture from a main feeding port of a twin-screw extruder, adding the second mixture from a side feeding port of the fifth section of the extruder, and adding the third mixture from a side feeding port of the sixth section of the extruder, and granulating after extrusion to obtain a material.

[0136] The extrusion temperature is 275° C. and the rotation speed is 550 r / min.

[0137] Comparative Example 1

[0138] The preparation method of this comparative example is basically the same as that of Example 1, except that: no SEPS is added to the raw material components, the same amount of SEBS is used, and other components are unchanged.

[0139] Comparative Example 2

[0140] The preparation method of this comparative example is basically the same as that of Example 1, except that LLDPE is not added to the raw material components, the same amount of HDPE is used, and other components are unchanged.

[0141] Comparative Example 3

[0142] The preparation method of this comparative example is basically the same as that of Example 1, except that: PP-R is not added to the raw material components, the same amount of homopolymer PP (PP-H) is used, and other components are unchanged.

[0143] Comparative Example 4

[0144] The preparation method of this comparative example is basically the same as that of Example 1, except that: Si-PC with a silicon content of 4-6% is not added to the raw material components, and the same amount of silicon PC with a silicon content of 20% is used, and other components remain unchanged.

[0145] Comparative Example 5

[0146] The preparation method of this comparative example is basically the same as that of Example 2, except that the phosphate flame retardant in the raw material component does not contain TPP, and the other components remain unchanged.

[0147] Comparative Example 6

[0148] The preparation method of this comparative example is basically the same as that of Example 2, except that the phosphate flame retardant in the raw material component does not contain RDP, and other components remain unchanged.

[0149] Comparative Example 7

[0150] The preparation method of this comparative example is basically the same as that of Example 2, except that the phosphate flame retardant in the raw material component does not contain HPCP, and the other components remain unchanged.

[0151] Comparative Example 8

[0152] The preparation method of this comparative example is basically the same as that of Example 3, except that the raw material components do not contain talcum powder, and the other components remain unchanged.

[0153] Comparative Example 9

[0154] The preparation method of this comparative example is basically the same as that of Example 3, except that the raw material components do not contain calcium carbonate, and the other components remain unchanged.

[0155] Comparative Example 10

[0156] The preparation method of this comparative example is basically the same as that of Example 3, except that the raw material components do not contain boehmite, and the other components remain unchanged.

[0157] Comparative Example 11

[0158] The raw material components of this comparative example are basically the same as those of Example 4, with the only difference being the preparation method and the second mixture of talcum powder, calcium carbonate and boehmite being added from the main feed port.

[0159] Comparative Example 12

[0160] The raw material components of this comparative example are basically the same as those of Example 4, except that: the preparation method, triphenyl phosphate (TPP), resorcinol bisdiphenyl phosphate (RDP) and hexaphenylepoxy triphosphazene (HPCP) are mixed according to mass fractions to obtain a third mixture, which is added from the main feeding port.

[0161] The properties of the PC composite materials prepared in the examples of the present invention and the comparative examples were tested.

[0162] See Table 2, which is a performance test data table of Examples 1 to 4 and Comparative Examples 1 to 12 of the present invention.

[0163] Table 2

[0164]

[0165]

[0166] As can be seen from the above table, in Comparative Example 1, no SEPS was added to the raw material components, and the same number of SEBS was used. Since SEBS does not contain propylene components, it cannot play a good compatibility role in materials containing PP and PE components like SEPS. The overall compatibility of the material is reduced, and both CTI and glow-wire performance are reduced.

[0167] In Comparative Example 2, LLDPE was not added to the raw material components, and the same amount of HDPE was used. PE can dilute the content of aromatic groups, and the degree of branching of HDPE is weak, which cannot better reduce the continuity of carbonization in three-dimensional space, so the CTI performance is significantly reduced.

[0168] In Comparative Example 3, the same proportion of homopolymer PP (PP-H) was used in the raw material components. PC as a non-crystalline material and PP-H with high crystallinity have large differences in aggregate structure during the molding process, and their compatibility is insufficient, so both CTI and glow-wire performance are reduced.

[0169] In Comparative Example 4, Si-PC with a silicon content of 4 to 6% was not added to the raw material components, and the same amount of Si-PC with a silicon content of 20% was used. The heat resistance of the material was significantly reduced, which was not conducive to the glow-wire performance, and the phase domain distribution of the dimethylsiloxane segment was too continuous, which could not effectively block the continuous carbonization during the CTI test. Therefore, both the CTI and glow-wire performances were reduced.

[0170] In comparative example 5, the phosphate flame retardant in the raw material components does not contain TPP, the charring efficiency in the flame retardant is relatively consistent, there is no charring time difference, and a continuous carbon layer is easily formed, which is not conducive to the CTI test, so the CTI performance has been significantly reduced.

[0171] In comparative example 6, the phosphate flame retardant in the raw material components does not contain RDP, the charring efficiency in the flame retardant is relatively consistent, there is no charring time difference, and a continuous carbon layer is easily formed, which is not conducive to the CTI test, so the CTI performance has been significantly reduced.

[0172] In comparative example 7, the phosphate flame retardant in the raw material components does not contain HPCP, the charring efficiency in the flame retardant is relatively consistent, there is no charring time difference, and a continuous carbon layer is easily formed, which is not conducive to the CTI test. Therefore, the CTI and glow-wire performances have been significantly reduced.

[0173] The raw material components of Comparative Example 8 do not contain talc, which cannot form partial water vapor at high temperature and destroy part of the carbon layer, so the CTI and glow-wire properties are significantly reduced.

[0174] The raw material components of Comparative Example 9 do not contain calcium carbonate, which cannot effectively dilute the aromatic content of the PC material and block the carbonization continuity of the material, so the CTI and flame retardant properties are reduced.

[0175] Comparative Example 10 does not contain boehmite in the raw material components. On the one hand, it does not act as a diluent to alleviate the effect of the phosphate flame retardant on PC degradation. At the same time, it cannot effectively improve the flame retardant properties of the material, so the CTI and glow-wire properties are reduced.

[0176] In the preparation method of Comparative Example 11, the second mixture of talc, calcium carbonate and boehmite is added from the main feed port, the dispersibility is poor, and the coating on the surface of the mineral is sheared, so the CTI and glow-wire performance are reduced.

[0177] In the preparation method of Comparative Example 12, triphenyl phosphate (TPP), resorcinol diphenyl phosphate (RDP) and hexaphenylepoxy triphosphazene (HPCP) are mixed according to mass fractions to obtain a third mixture, which is added from the main feeding port, reducing the effect of intermittent carbonization on the surface of the material, and thus the CTI performance is significantly reduced.

[0178] The above is a detailed introduction to a high CTI, high glow-wire flame-retardant PC composite material and a preparation method thereof provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and its core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including the manufacture and use of any device or system, and the implementation of any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A flame retardant PC composite material, characterized in that: Calculated by weight of raw materials, including:

2. The flame retardant PC composite material according to claim 1, characterized in that: The polycarbonate includes a polycarbonate polymerized by a phosgene method; The melt index of the polycarbonate is 40 to 60 g / min, and the test conditions are 300° C.×1.2 kg (ISO1133); The styrene mass content of the styrene-ethylene-propylene-styrene thermoplastic elastomer is 30% to 40%.

3. The flame retardant PC composite material according to claim 1, characterized in that: The silicon content of the silicon copolymer polycarbonate is 4% to 6% by mass; The melt index of the silicon copolymer polycarbonate is 8 to 15 g / 10 min, and the test conditions are 300° C.×1.2 kg (ISO1133); The phosphorus-based flame retardant includes triphenyl phosphate, resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene.

4. The flame retardant PC composite material according to claim 1, characterized in that: The polypropylene includes random copolymer polypropylene; The melt index of the polypropylene is 1-3 g / 10 min, and the test conditions are 230° C.×2.16 kg (ISO1133).

5. The flame retardant PC composite material according to claim 1, characterized in that: The polyethylene includes linear low-density polyethylene; The melt index of the polyethylene is 1-3 g / 10 min, and the test conditions are 230° C.×2.16 kg (ISO1133).

6. The flame retardant PC composite material according to claim 1, characterized in that: The calcium carbonate includes heavy calcium carbonate; The particle size of the calcium carbonate is 2.8 to 3.5 μm; The specific surface area of ​​the boehmite is 2.0 to 6.0 m 2 / g.

7. The flame retardant PC composite material according to claim 1, characterized in that: The talc powder includes ultrafine talc powder; The mesh size of the talcum powder is 5000-8000 meshes.

8. A method for preparing a flame retardant PC composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: 1) mixing polycarbonate, silicon copolymer polycarbonate, polypropylene, polyethylene, styrene-ethylene-propylene-styrene thermoplastic elastomer and a portion of phosphorus-based flame retardant to obtain a first mixture; Mixing calcium carbonate, talc and boehmite to obtain a second mixture; and mixing another portion of the phosphorus-based flame retardant to prepare a third mixture; 2) The first mixture obtained in the above step is added from the main feed port of the extruder, the second mixture is added from the side feed port of the middle section of the extruder, and the third mixture is added from the side feed port of the next section of the extruder. After extrusion and granulation, a flame retardant PC composite material is obtained.

9. The preparation method according to claim 8, characterized in that: The part of phosphorus-based flame retardant includes triphenyl phosphate; The other part of the phosphorus-based flame retardant includes resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene; The mass ratio of the triphenyl phosphate, resorcinol bisdiphenyl phosphate and hexaphenylepoxy triphosphazene is 1:1:

1.

10. The preparation method according to claim 8, characterized in that: The middle section is the fifth section of the extruder; The next section is the sixth section of the extruder; The extrusion temperature is 265-280°C; The extrusion speed is 500-600 r / min.

Citation Information

Patent Citations

  • High-CTI, high-heat-resistance, halogen-free and flame-retardant PC / ABS composition and preparation method thereof

    CN108129825A

  • High-CTI and low-temperature super-tough flame-retardant PC material and preparation method thereof

    CN111171548A